Severe Visual Impairments in Infants and Toddlers in the United States. (September 2013) - Hatton, Deborah D.; Ivy, Sarah E.; Boyer, Charles
Introduction: This article describes the most prevalent visual conditions and other demographic characteristics of 5, 931 young children with severe visual impairments in 28 states in the United States, the largest sample reported to date. The information presented in this article can assist in planning and implementing programs. Method: The data were collected at the time of entry into specialized early intervention programs for young children with visual impairments through reviews of records, interviews, and direct observations. They were sent to Babies Count: The National Registry for Children with Visual Impairments, Birth to 3 Years at the American Printing House for the Blind. The data were collected and entered between January 2005 and April 2011. Results: Cortical visual impairment, retinopathy of prematurity (ROP), and optic nerve hypoplasia were the three most prevalent diagnoses. Approximately 60% were identified as being legally blind, and 65% had disabilities in addition to visual impairments. The mean age of the children at the time of diagnosis was 4.9 (SD = 5.7) months, referral to specialized programs was at 10.5 (SD = 7.8) months, and entry into specialized programs was at 11.6 (SD = 8.0) months. There was an average lag of 5.6 months between the diagnosis and referral. Discussion: Cortical visual impairment, ROP, and optic nerve hypoplasia continue to be the leading causes of severe, uncorrectable visual impairments in children in the United States. ROP appears to be decreasing in prevalence; however, more children with ROP appear to have additional disabilities. The lag of 5.6 months between diagnosis and referral, a longer lag than was previously reported, is of concern. Implications for practitioners: Information about the characteristics of children with severe uncorrectable visual conditions is valuable for communicating with families, planning and implementing early intervention and educational programs, and collaborating with medical professionals.